Toxicological Effects of Aqueous Extract From African Walnut () Leaves in Rats - Seun F. Akomolafe PhD; Ganiyu Oboh PhD; Sunday I. Oyeleye MTech; Tosin A. Olasehinde MTech (SAGE Publishing, 2017)
Tetracarpidium conophorum leaves are used in traditional medicine for the treatment of male infertility, without considering its toxicity and side effects. In this study, we investigated the effects of T conophorum leaves on some biochemical parameters such as alanine aminotransferase, aspartate aminotransferase, bilirubin, albumin, creatinine, and uric acid. Histology of the liver and kidney were also assessed. The result revealed that the alanine aminotransferase and aspartate aminotransferase levels of the control group were not significantly different from the experimental groups. There was no significant difference in the albumin and bilirubin levels of the control and experimental groups. Similarly, the uric acid and creatinine levels of the experimental rats were not significantly different from the control. The examination of liver and kidney sections did not show any morphological changes and inflammatory cell infiltrations. These findings suggest that the leaves did not induce any pathological changes at the doses tested.